Deteksi Dini Perilaku Agresif pada Remaja - Nurmaya Febiurbaini; Syabila Syabila; Wika Nadilah; Risma Anita Puriani; Rizki Novirson (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Aggressive behavior in adolescents is a complex problem and can have an impact on emotional, social, and psychological development. The purpose of this study was to analyze the factors that influence individual aggressiveness and evaluate effective forms of intervention in dealing with it. This study used a literature study approach by analyzing 30 accredited national journals in the last five years. The results showed that aggressive behavior was triggered by external factors such as authoritarian parenting, excessive use of social media, and online game addiction. On the other hand, internal factors such as low self-control and inability to manage emotions also play a role. Early detection is an important step to identify risks early on. Interventions that have proven effective include educational programs, self-management-based group guidance, and individual counseling services. Collaboration between parents, education, and professionals is needed to create an environment that supports positive adolescent maturity and development.